Can elongation of the ileum by epiploic appendagitis result in acute abdomen? - Yıldırım, Doğan; Kocakuşak, Ahmet; Hut, Adnan; Çakır, Mikail (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Yıldırım D, Kocakuşak A, Hut A, Çakır M. Can elongation of the ileum by epiploic appendagitis result in acute abdomen? Turk J Gastroenterol 2018; 29: 370-2.